Paradigma Tafsir Egalitarianisme Zaitunah Subhan dalam Tafsir Kebencian - Khotimah, Husnul (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This article talks about Zaitunah Subhan's paradigm, which tries to interpret the verses on the equality of men and women with an egalitarian paradigm. The interpretation of the relationship between men and women, in general, is still dominated by the classical interpretation, which interprets women as originating from the rib of the Prophet Adam. This interpretation has implications for the marginalization of women as second-class creatures. The research results show that Zaitunah Subhan's paradigm in interpreting verses tends to follow the interpretation pattern of contemporary commentators such as Muhammad Abduh and Rasyid Ridha. In the context of Indonesian commentators, Zaitunah Subhan appears in line with the interpretations of Hamka, Quraish Shihab and Mahmud Yunus. These contemporary commentators do not agree with the meaning which states that women were created from the ribs of the Prophet Adam, but were created from one self (nafs wahidah). This meaning of Zaitunah Subhan has implications for opening up space for women to be able to live as equals as men. Men and women are essentially equal, except for devotion to God and the natural biological aspects that exist in women, that is the difference between men and women, more than that it is nothing but social ties that are deliberately created by patriarchy to marginalize women.